Computer-aided Diagnosis and Analysis of Skin Cancer from Dermoscopic Images in India - Brar, Khushmeen Kaur; Shiney, O. Jeba (Current Medical Imaging, 2024)
Background Researchers have made several advancements in this field, including automatic segmentation techniques, computer-aided diagnosis, mobile-based technology, deep learning methods, hybrid methods etc. All these techniques are beneficial in diagnosing melanoma or segregating skin lesions into different categories. Aim This paper aims to define different types of skin cancers, diagnosis procedures and statistics. This paper presents skin cancer statistics over a period of time in India. The increment in the number of skin carcinoma and melanoma cases from 1990 to 2020 as well as the mortality rates, has been presented in this paper. Also, this paper provides a review of different technologies used by researchers in detecting melanoma. Conclusion The rise in the number of cases by 2040 and mortality rates are compared. The statistics that are used in this paper are as per hospital-based cancer registries (HBCR) 2021 prepared by the Indian Council of Medical Research - National Centre for Disease Informatics and Research, Bengaluru (ICMR-NCDIR) and from World Health Organization (WHO).
Keywords: Skin carcinoma